Fabrication of redox-responsive magnetic protein microcapsules from hen egg white by the sonochemical method. (3rd October 2015) - Zhong, Shuangling; Cui, Xuejun; Tian, Fangyuan
Abstract: Redox-responsive magnetic protein microcapsules with Fe3 O4 magnetic nanoparticles (MNPs) encapsulated inside have been obtained using a facile, cost-effective and fast sonochemical method from hen egg white proteins. Such prepared redox-responsive magnetic hen egg white protein microcapsules (MHEWPMCs) could be easily manipulated to do magnetic-guided targeting delivery. The synchronous loading of the hydrophobic dye Coumarin 6 as a model of drug into MHEWPMCs was readily achieved during the fabrication of MHEWPMCs by dissolving them into the oil phase before ultrasonication. TEM images indicated that Fe3 O4 MNPs were encapsulated in MHEWPMCs. Confocal laser scanning microscopic images indicated that the dye was distributed evenly in the MHEWPMCs and no leakage of dye from the MHEWPMCs was observed due to the protection of protein shells. The MHEWPMCs are potential candidates as attractive carriers for drug targeting delivery and stimuli-responsive release due to their magnetic and redox responsiveness of the disulfide in the microcapsule shells.